National and Religious Types of Periphrases - Ahmadova Umidahon Shavkat Qizi (Researchparks Publishing, 2021)
The article shows that periphrastic units are one of the methodological tools that ensure the diversity and art of speech. Periphrases have a positive connotation in addition to expressing a certain concept, which means that they contain pragmasema, and with the help of these units, people's speech etiquette, culture of communication and society serve to make speech beautiful and fluent.